Kebiasaan Membaca dengan Kemampuan Menulis Resensi Siswa Kelas XI SMK Negeri 7 Palembang - Sulastri, Sulastri; Suryadi, Edi; Samaya, Doni (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to (1) find out the level of reading habits of class XI students at SMK Negeri 7 Palembang, (2) find out the level of ability to write reviews of class with the ability to write reviews for class XI students at SMK Negeri 7 Palembang. This research uses the correlation method. The population of this study was 385 class XI students at SMK Negeri 7 Palembang. The sample for this research was 30 students consisting of 9 men and 21 women. Data collection techniques use questionnaires and description tests. Data analysis used SPSS version 26. The results obtained by students showed that (1) the level of students' reading habits was good with an average of 79. The number of students in the very good category was 3 students (10%), in the good category there were 14 students (47% ), the medium category consists of 10 students (33%), and the poor category consists of 3 students (10%). (2) the level of students' review writing ability is in the "complete" category with an average of 76.3. There were 22 students in the "completed" category (74%) and (8%) students in the "incomplete" category. Based on the data obtained, there is a relationship between reading habits and the ability to write reviews of class So these results fall within the coefficient interval of 0.40−0.599. It can be stated that there is a relationship between reading habits and the ability to write reviews of class XI students at SMK Negeri 7 Palembang, which is in the medium category.